Complete genome sequence of Streptococcus agalactiae strain SA20-06, a fish pathogen associated to meningoencephalitis outbreaks. Issue 2 (March 2013) - Pádua Pereira, Ulisses; Santos, Anderson; Hassan, Syed; Aburjaile, Flávia; Castro Soares, Siomar; Ramos, Rommel; Carneiro, Adriana; Guimarães, Luís; Almeida, Sintia; Diniz, Carlos; Barbosa, Maria; Sá, Pablo; et al.
Abstract Streptococcus agalactiae (Lancefield group B; GBS) is the causative agent of meningoencephalitis in fish, mastitis in cows, and neonatal sepsis in humans. Meningoencephalitis is a major health problem for tilapia farming and is responsible for high economic losses worldwide. Despite its importance, the genomic characteristics and the main molecular mechanisms involved in virulence ofS. agalactiae isolated from fish are still poorly understood. Here, we present the genomic features of the 1, 820, 886 bp long complete genome sequence ofS. agalactiae SA20-06 isolated from a meningoencephalitis outbreak in Nile tilapia (Oreochromis niloticus ) from Brazil, and its annotation, consisting of 1, 710 protein-coding genes (excluding pseudogenes), 7 rRNA operons, 79 tRNA genes and 62 pseudogenes.